Komponen perancangan arsitektur lansekap : prinsip unsur dan aplikasi desain / Rustam Hakim ; editor, Dewi Ispurwanti, Dwi Nini Sutini - RUSTAM HAKIM; Dewi Ispurwanti; Dwi Nini Sutini (Bumi Aksara, 2014)
x, 383 hlm. ; 15 x 25 cm.